Implementing the Metaverse in Education: Survey Insights and Implications - El-Sayed, Ahmed; Hassan, Mona (CV TOPAZART, 2025)
This paper presents findings from recent survey-based studies exploring the adoption of metaverse technologies in educational settings. Drawing from empirical investigations in the UAE, insights from student perceptions, and comprehensive literature surveys, the article identifies key opportunities—including enhanced engagement, collaboration, and equity—alongside challenges such as cost, technological complexity, and privacy. The paper concludes with recommendations for pedagogical strategies, infrastructure investments, and policy considerations to support effective metaverse integration.